A note on the surface topography of profiled wood decking. Issue 2 (2nd April 2016) - Cheng, Kenneth J.; Evans, Philip D.
ABSTRACT: Profiled wooden deck-boards with small peaks and grooves machined into their surface are preferred in many countries to flat deck-boards because profiling makes the surface less slippery and prone to checking. Numerous companies manufacture profiled decking, and in this paper we examine the variation in topography of profiled wood decking. The topography of commercial profiled decking used in seven different countries was quantified using confocal profilometry, and principal components analysis was used to explore variability in topography between profiled decking samples and relationships between them. Confocal profilometry was able to measure the topography of profiled decking. We observed large variation in the height and width of profile peaks and also their peak and groove radii. Profiled decking can be classified into three morphological groups using the ratio of radii of surface grooves to those of peaks. Two of these groups, ribbed and rippled decking have been mentioned previously, but we identify and name a third group (ribble profile) with surface topography that lies between those of ribbed and rippled profiles. Our method of classifying profiles makes it possible to identify different types of profiled decking and provides a way of systematically comparing how profile topography influences the ability of profiles to restrict the checking of wood.